Treatment with granulocyte colony stimulating factor is associated with improvement in endothelial function - Ikonomidis, I.; Papadimitriou, C.; Vamvakou, G.; Katsichti, P.; Venetsanou, K.; Stamatelopoulos, K.; Papamichael, C.; Dimopoulos, A.-M.; Lekakis, J. (Growth Factors, 2008)
Primary objective: Granulocyte-colony stimulating factor (G-CSF) is used for the mobilization of bone marrow and endothelial progenitor cells, though G-CSF-induced inflammation may cause endothelial dysfunction. We examined the effects of G-CSF on endothelium, C-reactive protein (CRP), tumour necrosis factor-α (TNF-α) and anti-inflammatory cytokines namely interleukin 10 (IL-10). Research design: We studied 60 women with breast cancer, who were randomized to either subcutaneous G-CSF (5 μg/kg), o.d. for 5 days after adjuvant chemotherapy (n = 40) or placebo (n = 20). Experimental interventions: We measured flow-mediated dilatation (FMD%) of the brachial artery by ultrasonography, CRP, TNF-α, IL-10 and the ratio TNF-α/IL-10 blood levels before, 2-h and 5-days after the G-CSF or placebo treatment. Main outcomes and results: There was a greater increase of FMD, IL-10 and reduction of TNF-α/IL-10, 2 h and 5 days after the G-CSF treatment compared to placebo. Although, CRP and TNF-α were higher, TNF-α/IL-10 was lower at the end of G-CSF treatment compared to placebo. Improvement of FMD was related to changes of IL-10 and TNF-α/IL-10. Conclusions: Treatment with G-CSF improves endothelial function in vivo, possibly by shifting the balance between the pro- and anti-inflammatory cytokines.
Keywords: CRP; Endothelium; Granulocyte colony stimulating factor; Interleukins